ANALISIS ENERGI DAN EKSERGI PENGERINGAN LAPISAN TIPIS TEMU PUTIH - Manalu, Lamhot P.; Tambunan, Armansyah H.; Nelwan, Leopold O.; Hoetman, Agus R. (185P -3466)
This paper is concerned with the energy and exergy analyses of the thin layer drying process of temu putih (Curcuma zedoaria (Berg.) Rosc) at three different air temperatures (40, 50 and 60 oC) and air relative humidities (RH 20%, 40% and 60%) using a laboratory dryer. Using the first law of thermodynamics, energy analysis was carried to estimate the amounts of energy gained from air drying and the ratios of energy utilization. However, exergy analysis was accomplished to determine exergy losses and exergy efficiencies during the drying process by applying the second law of thermodynamics. The values of energy and exergy efficiencies were found to be in the range of 23.5 - 49.1% and 3.8-14.1% from 40 to 60 oC, respectively, while from RH 20% to 60% its values are 48.4-62.8% and 13.6-14.6%, respectively.